2022
DOI: 10.1049/mna2.12104
|View full text |Cite
|
Sign up to set email alerts
|

Development of an environmentally friendly nanoemulsion based on Ginkgo biloba exocarp extracts to control Plutella xylostella

Abstract: The chemical compositions of Ginkgo biloba exocarp extracts (GBEE) and leaf extracts are similar, however, studies describing the development of GBEE biopesticides are few. In this study, the authors investigated the preparation of GBEE nanoemulsionand and characterized by transmittance, physical stability, droplet size and size distribution for the first time. Insecticidal activity and lipophilicity screening of four different solvents indicated ethyl acetate was satisfactory. Based on dispersibility, centrif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…These findings highlight the superior insecticidal potency of the GBEE nanoemulsion compared to the GBEE leaf extracts. 175 Abdelmaksoud et al reported the effectiveness of emulsifiable concentrates (EC) and nanoemulsions derived from the essential oils of Salvia officinalis and Melissa officinalis in combating Aphis craccivora and Liriomyza trifolii . The outcomes revealed that the nanoemulsion of S. officinalis notably decreased the population of A. craccivora by 86.64%, followed by M. officinalis at 76.67%.…”
Section: Nanoemulsions: Transformative Insecticidal Formulation For T...mentioning
confidence: 99%
“…These findings highlight the superior insecticidal potency of the GBEE nanoemulsion compared to the GBEE leaf extracts. 175 Abdelmaksoud et al reported the effectiveness of emulsifiable concentrates (EC) and nanoemulsions derived from the essential oils of Salvia officinalis and Melissa officinalis in combating Aphis craccivora and Liriomyza trifolii . The outcomes revealed that the nanoemulsion of S. officinalis notably decreased the population of A. craccivora by 86.64%, followed by M. officinalis at 76.67%.…”
Section: Nanoemulsions: Transformative Insecticidal Formulation For T...mentioning
confidence: 99%